Effect of the inclusion of SUBTILPROBIO® zootechnical additive in the production of different livestock categories in Matanzas. Technical note - Milián, Grethel; Beruvides, A.; Pérez, Y.; Rodríguez, Marlén; Rondón, Ana J.; Pérez, M. L.; Placeres, Iraní (Cuban Journal of Agricultural Science, 2022)
The impact that the use of the nutritional additive SUBTILPROBIO® has on the feeding of different livestock categories is exposed: laying hens L33, Heavy Pure Lines E1 and B4, Yorkshire - Landrace x L35 pigs, in breeding, pre-fattening and fattening, and small ruminants. The research was carried out at different times and enterprices in Matanzas territory: Combinado Avícola, Empresa Genética Avícola and Pie de Cría, Unidades Porcinas and Empresa Pecuaria Genética de Matanzas, Cuba. This additive was made with the strains Bacillus subtilis subspecies subtilis C-31, C-34 and E-44 at a concentration of 109 cfu/g. The results showed increases in the productive indicators: live weight, intake, conversion, egg production, decrease in cracked and disqualified eggs, economic benefits for weight concepts. The health indicators showed positive results for mortality, viability, death by pecking or cannibalism, decrease in the presence of bacterial and immunological diseases. The effectiveness of the zootechnical additive SUBTILPROBIO® was showed as an alternative in livestock production. Key words: nutritional additives, Bacillus endospores, animal feeding, antibiotics, probiotics